HUBUNGAN PANJANG TUNGKAI DAN DAYA LEDAK OTOT TUNGKAI DENGAN PRESTASI LOMPAT JAUH PADA SISWA PUTRA KELAS VII SMPN 1 SUMBAWA - Sapwaturrahman Sapwaturrahman; Dadang Warta Candra Wira Kesuma; Elya Wibawa Syarifoeddin (Universitas Pendidikan Mandalika, 2020)
The length of the legs and the explosive power of the leg muscles are very important factors or elements for obtaining a good long jump achievement. This study aims to determine: 1) the relationship between leg length and long jump achievement; 2) the relationship between leg muscle explosive power and long jump performance; and 3) the relationship of leg length and leg muscle explosive power with long jump achievement in seventh grade male students of SMPN 1 Sumbawa for the 2019/2020 academic year. This study used survey research methods, observation, documentation and data collection techniques using tests and measurements which were analyzed using multiple linear correlation analysis using the product moment correlation formula and multiple correlation with the population used as research subjects as many as 32 students. The results of data analysis in this study indicate that: 1) in the relationship (correlation) to, it was found that the calculated r-value was greater than the r-table value, namely 0.852> 0.433, meaning that